Lifestyle Assessment: Testing the FANTASTIC Instrument - Wilson, Douglas M. C. (1984)
This is the third in a series of six articles on lifestyle assessment. The clinician's confidence in an assessment instrument increases with use, appropriate revision based on a review of the current literature, reliability and validity testing. The FANTASTIC lifestyle assessment instrument, described in Part 1 of this series, has undergone such testing. This article describes preliminary use and testing of the FANTASTIC questionnaire, its use in a community health education program, and current reliability and validity studies of the microcomputer version.